2008
DOI: 10.1007/s00192-008-0593-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and ultrasonographic correlations following three surgical anti-incontinence procedures (TOT, TVT and TVT-O)

Abstract: The aim of this study was to compare ultrasonographic findings on tape position, angulation and mobility following three surgical anti-incontinence procedures (trans-obturator tape (TOT), tension-free vaginal tape (TVT), tension-free vaginal tape obturator (TVT-O)) and to correlate these data with clinical signs of cures and failures and de novo voiding disorders. In this prospective study, vesicourethral static and dynamic analysis of 81 patients (30 TOT, 28 TVT, 23 TVT-O) were evaluated using introital ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 24 publications
2
34
0
5
Order By: Relevance
“…Chene et al have compared the vesicourethral dynamics and explored the correlations between surgical outcomes and axial tape angulations by ultrasound after TOT and RPT procedures [12]. They observed a wider straining axial tape angle, a manifestation suggesting mechanical compression of the urethra by the tape [12]. They also reported the associations between a wider resting tape angulation and recurrent SUI, narrower squeezing tape angulation and de novo urgency incontinence, and narrower straining tape angulation and postoperative voiding disorders [12].…”
Section: Commentmentioning
confidence: 94%
See 2 more Smart Citations
“…Chene et al have compared the vesicourethral dynamics and explored the correlations between surgical outcomes and axial tape angulations by ultrasound after TOT and RPT procedures [12]. They observed a wider straining axial tape angle, a manifestation suggesting mechanical compression of the urethra by the tape [12]. They also reported the associations between a wider resting tape angulation and recurrent SUI, narrower squeezing tape angulation and de novo urgency incontinence, and narrower straining tape angulation and postoperative voiding disorders [12].…”
Section: Commentmentioning
confidence: 94%
“…They observed a wider straining axial tape angle, a manifestation suggesting mechanical compression of the urethra by the tape [12]. They also reported the associations between a wider resting tape angulation and recurrent SUI, narrower squeezing tape angulation and de novo urgency incontinence, and narrower straining tape angulation and postoperative voiding disorders [12]. The data are represented with number (percentage) and analyzed with Yates corrected Chi-square test.…”
Section: Commentmentioning
confidence: 95%
See 1 more Smart Citation
“…The importance of the urethrovesical junction (UVJ) and proximal urethra (PU) mobility in the maintenance of female urinary continence has already been established [4,[6][7][8][9][10][11] . However, the urodynamic evaluation determines only indirectly the UVJ and PU mobility, differently from what can be clearly demonstrated in real time imaging by ultrasound [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] .…”
mentioning
confidence: 99%
“…The ultrasonographic examination of the UVJ and PU has been increasingly used in the preoperative evaluation and postoperative follow-up of patients with SUI, to document the UVJ and PU positioning before and after the elected surgical treatment [4][5][6][7][8][9][10][11][12][13][17][18][19] . At least one study suggested that the positioning of the UVJ and PU in the postoperative period is a good marker for treatment prognosis (whether a surgical procedure for SUI correction had been successful or not) [14] .…”
mentioning
confidence: 99%